Agapetes guangxiensis D. Fang (Ericaceae), a new record for the flora of Vietnam - Thanh Huong, Nguyen Thi; Hua, Tong Yi; Chinh, Vu Tien; He, Xia Nian; Phuong Anh, Tran Thi (Academia Journal of Biology, 2015)
Agapetes guangxiensis D. Fang, previously known only from China, is reported here as a new record for the flora of Vietnam. This species was discovered in Dien Bien province and Ha Giang province, North Vietnam. It differs from the closed relative species, A. rubrobracteata, in having leaf blades ovate with serrate margins, inlforescence barcts small (ca. 0.5 mm long) and anthers ecalcarate. Detailed information on the taxonomy, type, ecology and distribution are provided for A. guangxiensis. The vouchers of this speices that we studied are housed at the herbarium of Institute Ecology and Biological Resources, Hanoi, Vietnam (HN). A key to the nine species of Agapetes that are now recognized for Vietnam is provided